A Success Story of Cerebral Arteriovenous Malformation (AVM) Treated with Stereotactic Radiosurgery (SRS) in Bangladesh - Kumar, Narendra; Yasmin, Taohida; Appasamy, Murugan; Rana, KM Masud; Kumar, R Arun; Joardar, Aliuzzaman; Ahsan, Sania; Alam, Saiful (Bangladesh Journal of Neurosurgery, 2023)
Purpose: To share a case of cerebral Arteriovenous Malformation (AVM) patient, treated with Stereotactic Radiosurgery (SRS) at Evercare Hospital Dhaka, treatment process and successful outcome. Background: Arteriovenous malformation is an anomaly, mostly congenital due to a misfit in vasculogenic, where arteries and veins come to a direct connection. Treatment options include observation, embolization, microsurgery, Stereotactic Radiosurgery (SRS) either alone or in combination. This report describes our experience in treating a patient of AVM by SRS. Stereotactic Radiosurgery is an established modality to achieve desired nidus obliteration, excellent compliance being noninvasive, and reduced treatment-related morbidity. This case report also reviewed the literature in detail. After a thorough literature search, to the best of our knowledge, this shall be the first published case report of AVM successfully treated with SRS in Bangladesh. Case Presentation: In March 2019, 25-years old male presented in Radiation Oncology OPD as a diagnosed case of AVM, having complaints of headache for two years. Headache was occasional and often associated with vertigo and dizziness. He had no neurologic deficit. A radiological assessment revealed a large (4.6x4.4cm) AVM in the left parieto-occipital lobe showing serpiginous enhancement with IV contrast. After routine workup, he underwent stereotactic Radiosurgery in March’2019. A dose of 23Gy was delivered to the malformation, including all nidus. Acute radiation toxicity was noted as transient hair loss only over the irradiated area and no other side effect. Radiological Assessment was done at six months, 1year, and 2.5 years. After having a stable size at six months, complete nidus obliteration was achieved at one year. His last visit to our OPD was in July 2021, with radiologically complete nidus obliteration without any significant clinical symptoms. Conclusions: Linear Accelerator-based SRS is an excellent treatment option for AVM, encouraging clinical outcomes for carefully selected patients. Bang. J Neurosurgery 2022; 12(1): 53-64